1083 The Highly Selective Sigma-1 Receptor Agonist Pre-084 Reduces Inflammation-Sensitized Hyperoxia-Induced Injury in the Developing Rat Brain. (October 2012) - Posod, A; Krepp, Y; Neubauer, V; Wegleiter, K; Urbanek, M; Keller, M; Kiechl-Kohlendorfer, U; Griesmaier, E
Abstract : Background: Supraphysiologic oxygen concentrations are toxic to the developing brain. Inflammatory processes increase the risk of brain injury. We have previously shown a protective effect of dextromethorphan, a NMDA receptor antagonist and sigma-1 receptor (σ1R) agonist, in an animal model of hyperoxia-induced neonatal brain injury. In adult brain injury, sigma agonists have a proven therapeutic potential. Aim: To assess the highly selective σ1R agonist PRE-084 in a newborn animal model of inflammation-sensitized hyperoxia-induced brain injury. Methods: Rat pups were randomly pre-sensitized with a single intraperitoneal (ip) injection of i) LPS or ii) vehicle on postnatal day 3. On postnatal day 5, pups were ip-injected with i) PRE-084 1µg/g bodyweight or ii) vehicle and were subsequently subjected to either i) hyperoxia (HX, FiO2>0.9) or ii) normoxia (NX, FiO2=0.21) for 24 hours. At the end of exposure, animals were sacrificed and brains were processed for caspase-3 analysis using immunohistochemistry and Western Blotting. Results: A single LPS injection significantly increased the number of activated caspase-3-positive cells in cortical grey matter after hyperoxic exposure, which was reduced by PRE-084 administration (mean number of cells ±SEM; LPS_NX_vehicle 31.26±1.29 vs. LPS_HX_vehicle 38.11±1.13, p<0.01 vs. LPS_HX_PRE-084 33.66±1.54, p<0.05; n=6–7). Western Blot analyses showed a strong reduction in caspase-3 cleavage in PRE-084-treated pups compared to vehicle-injected controls in both pre-sensitized and non-pre-sensitized animals after hyperoxic exposure. Conclusion: PRE-084 reduces inflammation-sensitized hyperoxia-induced injury in the developing rat brain by inhibition of apoptosis. Sigma agonists are a potential therapeutic approach in perinatal brain injury and merit further studies.